PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, SISTEM PENGENDALIAN INTERNAL DAN GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH (STUDI PADA SKPD KOTA BANDUNG) - Fitria, Fitria (Review of Accounting and Business, 2024)
This research aims to determine the effect of the implementation of government accounting standards, internal control systems, and good governance of government financial reports in SKPD (Regional Work Units) of Bandung City. The research method used in this research is a quantitative method with a descriptive and verification approach, while the data collection technique is carried out by distributing questionnaires to respondents, especially the head of the finance sub-division and finance section staff at SKPD Bandung City, the sample collection technique uses non-probability sampling specifically purposive sampling technique. Based on the calculation results, the coefficient of determination shows that the implementation of government accounting standards, internal control systems, and good governance has a 49% explanation on the quality of government financial reports in SKPD of Bandung City, the remaining 51% is attributed to other variables not examined in this study.